Fast Transitions of X-Ray Variability in the Neutron Star Low-mass X-Ray Binary Cygnus X-2 - Liang Zhang; Mariano Méndez; Hua Feng; Diego Altamirano; Zi-xu Yang; Qing-chang Zhao; Shuang-Nan Zhang; Lian Tao; Yue Huang; Xiang Ma; Shu-mei Jia; Ming-yu Ge; et al. (The Astrophysical Journal, 2025)
We present a spectral-timing analysis of two NICER observations of the weakly magnetized neutron star low-mass X-ray binary Cygnus X-2. During these observations, we detect a rapid transition from a narrow 50 Hz horizontal-branch oscillation (HBO) to a broad 5 Hz normal-branch oscillation (NBO), accompanied by an increase in source flux and a decrease in spectral hardness. Thanks to the large effective area of NICER, we are able to conduct a detailed comparison of the spectra associated with different types of quasiperiodic oscillations (QPOs) on short timescales. By fitting the spectra with a model that includes a disk and Comptonization components plus two emission lines, we find that the parameters of the disk component do not change significantly during the transition. However, assuming a fixed electron temperature, the optical depth of the Comptonization component decreases significantly. This drop in optical depth may be attributed to the expansion of the boundary layer (BL) or spreading layer (SL). In addition, we find that the rms spectra for both the HBOs and NBOs are hard, suggesting that the BL or SL is driving the variability. We discuss the potential physical origin of the different types of QPOs.